Analysis of Threaded-Type Integrated Learning Model in Developing Creativity and Critical Thinking - Rahmah, Zaza Bella Ummi; Kamaliyah, Ratu Bulkis (LPPM Universitas Terbuka, 2024)
Teaching and learning activities in elementary schools prioritize mastery of material or theory-based. This research aims to evaluate the effectiveness of the Threaded-type integrated learning model in developing the creative thinking skills of elementary school students, which is one of the essential skills in the 21st century. This study is intended to identify the extent to which the application of the Threaded-type integrated learning model supports the development of students' thinking creativity. This type of research is a literature study that collects secondary data by exploring various literature from articles from nationally accredited and reputable international scientific journals. The results of the study show that the Threaded-type integrated learning model can be applied in elementary schools and is effective in encouraging students to think creatively. This model facilitates students in connecting various learning concepts thoroughly, thereby enriching their thinking process and creativity Keywords: integrated learning, threaded, creative thinking